Effects of economic policies on microeconomic volatility - Cournède, Boris (OECD Publishing, 2015)
Economic policies shape how much people earn, as well as how stable their income and jobs are. The level and stability of earnings both matter for well-being. Standard economic aggregates do not measure accurately the economic uncertainty which households are facing. This paper shows that household-level economic instability is only very loosely related to macroeconomic volatility. It uses several household-level databases to document how structural reforms aimed at boosting growth influence household-level economic stability. Movement from less to more productive processes and firms is at the heart of economic growth, which suggests a trade-off between growth and micro-level stability. Certain policy changes boost growth but increase micro-level instability: they include reductions in tax progressivity or social transfers (including unemployment benefits), as well as moves from very to moderately tight restrictions on the flow of goods and services and on the firing of regular workers. However, the analysis also uncovers that moving to highly competitive policies in general reduces micro-level instability. This finding points to a case for comprehensive rather than marginal reform in tightly regulated countries, since a comprehensive agenda can deliver higher growth without the instability costs that a more marginal reform can entail. JEL classification: D12, D22, J08, O40 Keywords: Stability, households, economic growth, reforms, microdata